HUBUNGAN POLA MAKAN, AKTIVITAS FISIK, DAN DURASI TIDUR DENGAN KEJADIAN GIZI LEBIH PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA - Indy Surya Putri, (2020)
The prevalence of being overweight in Indonesia based on Riskesdas 2007 - 2018 continues to increase. More nutritional status in health students is still found in several studies in several universities. This study aims to determine the relationship between eating patterns, physical activity, and sleep duration with the occurrence of over nutrition in Faculty of Health Science of UPN Veteran Jakarta students. This study uses a cross-sectional design and purposive sampling technique with a sample of 62 respondents. Anthropometric data obtained through self-reported respondents, eating patterns obtained through FFQ, physical activity data using the Baecke questionnaire (1992), sleep duration using STQ (2012). Relationship analysis was performed using the chi-square test and showed the results that there was a relationship between eating patterns of staple food categories with the incidence of over nutrition (p = 0.016). There was no relationship between diet (animal protein (p = 1.00), vegetable protein (p = 0.08), vegetables (p = 0.99), fruit (p = 0.88), sweet drinks (p = 0.97), fast food (p = 0.26)), physical activity (p = 0.95), and duration of sleep (p = 0.73) with the occurrence of over nutrition in Faculty of Health Science of UPN Veteran Jakarta students. Eating patterns in accordance with the guidelines for balanced nutrition, increased physical activity, and adequate sleep duration are recommended in order to reduce the number of over nutrition.